Dalbavancin treatment for spondylodiscitis: multi-center clinical experience and literature review. (20th September 2022) - Ramadan, Mohammad Said; Gallo, Raffaella; Lugarà, Marina; Gambardella, Michele; Oliva, Gabriella; Bertolino, Lorenzo; Andini, Roberto; Coppola, Nicola; Zampino, Rosa; Durante-Mangoni, Emanuele
Abstract: Dalbavancin is a novel lipoglycopeptide antibiotic, characterized by a broad spectrum of activity against Gram-positive cocci. However, its efficacy in spondylodiscitis treatment is not fully established. All adult patients diagnosed with spondylodiscitis and treated with dalbavancin were included across four Italian medical centers from January 2018 to April 2021. We collected clinical and laboratory data, and presented follow-up findings along with a thorough literature review. 13 patients (mean age= 65 years) were included in this study. Dalbavancin was administered as first line treatment in six (46%) of the patients. Reasons for using Dalbavancin included treatment simplification (62%) and clinical failure of previous antibiotics (23%). In general, Dalbavancin was well tolerated with minimal adverse events, and clinical success was achieved in 11/13 (85%) of the patients during hospitalization with additional antibiotics required in the remaining two cases. Five months after discharge, no mortality was observed, however, 42% of patients required additional antibiotics for signs of infection on follow-up imaging. Our study suggests that Dalbavancin could be an effective and safe option in treating spondylodiscitis, however, the scarcity of studies on the topic is concerning. Thus, further studies with large samples and long-term follow-up are warranted to compare the efficacy of Dalbavancin with other available treatment options.